Multilevel Marketing: Peluang atau Ancaman - Handi Lesmana (Bina Ekonomi, 1999)
Multilevel marketing (MLM) has become a part of the world's economy. It has grown rapidly and has spread all over the world. MLM arrived in Indonesia in 1984. At the moment, the number of MLM members in Indonesia has reached three million. Lately, MLM malpractices (money games) have become a hot topic in Indonesia. This paper will discuss MLM and its differences from the "money game business".